2001
DOI: 10.1007/3-540-45541-8_1
|View full text |Cite
|
Sign up to set email alerts
|

“What Is a Petri Net?” Informal Answers for the Informed Reader

Abstract: The increasing number of Petri net variants naturally leads to the question whether the term "Petri net" is more than a common name for very different concepts. This contribution tries to identify aspects common to all or at least to most Petri nets. It concentrates on those features where Petri nets significantly differ from other modeling languages, i.e. we ask where the use of Petri nets leads to advantages compared to other languages. Different techniques that are usually comprised under the header "analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…This process is iterated to yield a Petri net model that is consistent with the genetic model. Desel and Juhas [2001], Petri nets are a type of directed graph that can be used to model discrete dynamical systems. Goss and Peccoud [1998] demonstrated that Petri nets could be used to model molecular interactions in biochemical systems.…”
Section: Biological Systems Modeling Of Epistasismentioning
confidence: 99%
“…This process is iterated to yield a Petri net model that is consistent with the genetic model. Desel and Juhas [2001], Petri nets are a type of directed graph that can be used to model discrete dynamical systems. Goss and Peccoud [1998] demonstrated that Petri nets could be used to model molecular interactions in biochemical systems.…”
Section: Biological Systems Modeling Of Epistasismentioning
confidence: 99%
“…Hyperedge h must only leave and enter BASIC nodes that are in its source and target set; otherwise, the configuration reached after taking h in C does not correspond to the marking reached by firing isomorphic transition f −1 (h) in M . This implies that in the statechart no additional BASIC nodes are left or entered by taking h. This corresponds to the Petri net locality principle [DJ01] that states that each transition can only consume tokens from places in its preset and only produce tokens for places in its postset.…”
Section: Statecharts Corresponding To Statechartable Netsmentioning
confidence: 99%
“…So BASIC node n4 is left even though it was not a source of h5. In Petri nets, such behaviour is impossible due the locality principle [3], which states that each transition can only consume tokens from places that are in its preset. Thus, mapping a transition to a hyperedge with an in- complete source set does not preserve behaviour.…”
Section: Processing Of Transitionsmentioning
confidence: 99%